Traces of Inconclusiveness: Polysemy and Ambiguity in King Lear - David Correia de Araújo Ericeira (2019)
Set in a supposed ancient Britain, King Lear materializes the anxieties of Early Modern England through a tendency towards ambiguity that characterizes the play's polysemic construction and, by consistently challenging any assurances regarding the human condition, it brings about a growing sense of inconclusiveness that culminates in its bleak ending. The major objective is to demonstrate how King Lears polysemy is built upon ambiguous uses of language as the moments of irresolution in the play grow stronger. In order to do so, other important objectives are contemplated throughout this Masters thesis. Epitomized by ambiguous and paradoxical utterances, the plays polysemic construction is scrutinized to reveal in under what conditions: the process of cultural analysis affects the textual devices; the tendency towards ambiguity generates the sense of inconclusiveness; and the recurrent betrayal of expectations concerning the plot reflects the correspondence between the tragic ending and the indeterminacy derived from the dramatic rhythm. Finally, it is analyzed how specific passages that bring about the drama of finitude not only confront the plays desolate atmosphere, but they are also at the core of an implicit concern about what is left regarding the human condition.